P044 Primary care management of chronic insomnia by general practitioners: an Australian perspective. (7th October 2021) - Grivell, N; Haycock, J; Redman, A; Saini, B; Vakulin, A; Lack, L; Lovato, N; Sweetman, A; Zwar, N; Stocks, N; Franks, O; Mukherjee, S; et al.
Abstract: Introduction: Chronic insomnia is a common sleep disorder, with an estimated 15% of Australian adults reporting symptoms of insomnia. Australian general practitioner (GP) guidelines recommend cognitive behavioural therapy for insomnia (CBTi) as first-line treatment for insomnia however research suggests that GPs instead rely heavily on sleep hygiene and pharmacotherapy. GPs commonly provide treatment for insomnia; however, little is known about the experiences of Australian GPs and their interest when managing patients with insomnia. This study was conducted to explore the perspectives of GPs towards insomnia management and to identify factors that could influence the implementation of new models of insomnia care within general practice. Methods: A pragmatic, inductive qualitative study. Purposive sampling was used to recruit 28 Australian GPs varying in age, experience, and distance from specialist sleep services. Semi-structured interviews were conducted, and data were analysed using thematic analysis. Results: Three themes were identified: 1) Responsibility for insomnia care; 2) Complexities in managing insomnia; and 3) Navigating treatment pathways. Whilst GPs accepted insomnia care as part of their role, they often found it difficult to provide evidence-based care within the time and funding limitations of general practice. Co-morbidity of mental health conditions and insomnia, and long-term use of benzodiazepines presented challenges for GPs. GPs' knowledge and experience of CBTi and access to specialised referral pathways for insomnia was limited. Discussion: Insomnia presents complexities for GPs. Education about insomnia treatments, funding that enables recommended treatment, and pathways to specialist services would support insomnia management within general practice.